PENGARUH SIZE, LIKUIDITAS, PROFITABILITAS, RISIKO, DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL - Siti Hardanti; Barbara Gunawan (Journal of Accounting and Investment, 2010)
This research was carried out to test the influence of the size, liquidity, profitability, risks and sales growth towards the simultaneously and partially capital structure. The object of this research was all manufacture industries listed in Indonesian Stocks Exchange (ISE). The sample of this research was 71 manufacture industries selected using the purposive sampling technique which was based on three criteria: 1) the manufacture industries that were listed and active in the Indonesian Stock Exchange during the research period; 2) The companies had positive profits during the research period; 3) The manufacture companies that must have complete data in Indonesian Capital Market Directory (ICMD). The research data were secondary data which were obtained from ICMD in the years of 2005-2008 in the ISE UMY Corner. The result of analysis showed three findings. 1) Simultaneously, the size, liquidity, profitability, risks, and sales growth influence the capital structure. 2) Partially, the size gave positive and significant influence towards capital structure, while the liquidity and profitability gave negative significant influence towards the capital structure. 3) Partially, the risks and sales growth did not influence the capital structure.